Analysis of visitor attendance at Polish tourism attractions - Kruczek, Zygmunt (Turyzm/Tourism, 2015)
Tourism attractions are an important segment of the tourism market; they play an immense role in shaping the geography of the tourism movement. In spite of that studies devoted to tourism attractions are undertaken relatively rarely. In the present article, the author presents the results of research devoted to attendance at various types of tourism attraction in Poland, along with an attempt to identify the factors determining their popularity which is measured by the number of visitors. Among others, the author distinguishes the so-called flagship attractions which are of importance for the identity and general image of individual regions.